Pengaruh Motivasi dan Kompensasi terhadap Kinerja Karyawan pada Perseron Terbatas Digitdata Terminal Evolusi - Dahrul Siregar (Journal of Education, Humaniora and Social Sciences (JEHSS), 2019)
This study aims to determine the "Effect of Motivation and Compensation on Employee Performance at PT Digitdata Terminal Evolution". The type of data in this study is associative, namely a study that is asking about the relationship between two variables. The population in this study were 35 employees in PT Digitdata Terminal Evolusi. The data collection technique is in the form of distributing questionnaires to office employees at PT Digitdata Terminal Evolusi. Data analysis techniques use validity and reliability tests, hypothesis testing, statistical tests using multiple linear analysis models using multiple linear analysis models and determination tests.Based on the results of the study, the Motivation variable has a positive and significant effect on the performance variable and the compensation variable partially has a positive and significant influence on the performance variable. While partially motivation and compensation simultaneously have a positive and significant effect on performance variables activation.